ANALISIS KANDUNGAN ESCHERICHIA COLI PADA AIR MINUM DI DEPOT PENGISIAN AIR ISI ULANG DI DESA TUNTUNGAN - Egi Dewanata Putra; Irdina Maharani, Kyky Sartika Sari, Abdurrozaq Hasibuan (CV. ADIBA AISHA AMIRA, 2024)
Water is a very important element for the survival of all living things on this earth. Water is the beginning of human life and also for animals and plants. For the human body, water has an important role as a source of nutrition for the body. One type of water that is needed by humans is drinking water. Drinking water is water that has been processed and also treated with a processing process that meets health requirements, so that this water is possible to drink directly. The people in Tuntungan Village fulfill their drinking water needs by buying drinking water from the Refill Drinking Water Depot (DAMIU). The water at the depots around Tuntungan Village is sourced from springs in the Sibolangit area, North Sumatra, where this water is distribute using tank trucks to drinking water depots in Tuntungan Village. Then it will be processed and distributed in each water depot. The drinking water treatment process at DAMIU has the potential to cause water to contain E.coli. Therefore, this research was conducted to determine whether there was E. coli in the water distributed by DAMIU in Tuntungan Village. This research is an experimental research combined with a cross sectional approach. The number of samples in this study were 5 drinking water samples taken from 5 different DAMIUs using a purposive sampling technique. Sample examination was carried out at the UPT Health Laboratory of the North Sumatra Provincial Health Office on Jl. Willem Iskandar Pasar V Barat 1 (Jl. Balai Pom) No. 4. The results showed that there were 3 samples of drinking water that were positive for E.Coli and 2 samples that were negative for E.coli